THE ANTONYM OF LEXEME USING THE AFFIXATION â€˜ME-KANâ€™: MORPHOSEMANTICS ANALYSIS - Anis, Muhammad Yunus; Saddhono, Kundharu (Universitas Pendidikan Indonesia, 2016)
AbstractThis research deals with morphosemantic analysis of lexemes. The main source of data in this research was taken from the Arabic-Indonesian dictionary, Al-Munawwir, with the primary focus on lexemes using the affixation of â€œme-kanâ€. The lexemes with affixation â€œme-kanâ€ can be compared in the Arabic language using the dominant measure or pattern (wazan). This research adopts a qualitative descriptive analysis, employing the distributional approach and the technique of dividing units of language, as well as the technique of marker. The study shows that the lexemes using affixation â€œme-kanâ€ in Indonesian have similarities with the wazan fa-â€˜a-la in Arabic. The affixation of â€œme-kanâ€ is one of the forms of transitive verb in the Indonesian language, and wazan fa-â€˜a-la in Arabic is a form of taâ€™diyyah (close meaning with the transitive form). Many lexemes using the affixation â€œme-kanâ€ in Al-Munawwir Indonesianâ€“Arabic dictionary were translated by the wazan fa-â€˜a-la. This study indicates that there is a strong connection between the transitive form in Arabic and Indonesian, as indicated through the analysis of the aforementioned lexemes.Keywords: antonym, lexeme using the affixation of â€œme-kanâ€, morpho-semantics, and Al-Munawwir Indonesian-Arabic dictionary.Â Â AbstrakÂ Sumber data dalam penelitian ini diambil dari kamus Al Munawwir versi Indonesia-Arab. Pembahasan antonim di dalam kamus tersebut masih terasa luas, belum mengerucut. Oleh sebab itulah peneliti akan memfokuskan pembahasan antonim hanya pada leksem yang mendapat imbuhan â€œme-kanâ€. Selanjutnya leksem â€œme-kanâ€ di dalam bahasa Indonesia ternyata memiliki padanan wazan(measure) di dalam bahasa Arab yang sangat dominan. Penelitian ini menggunakan model penelitian deskriptif kualitatif dengan menggunakan metode distribusional dan teknik bagi unsur langsung dan teknik pemarkah. Dengan memanfaatkan metode tersebut, maka penelitian secara masif di dalam kamus tersebut akan menemukan pemakaian wazan untuk leksem berimbuhan me-kan dengan frekuensi lebih banyak dibandingkan dengan wazan lainnya. Sehingga imbuhan me-kan pada bahasa Indonesia dapat ditemukan padanannya pada wazan bahasa Arab. Beberapa data berupa leksem berimbuhan â€œme-kanâ€ di dalam kamus al munawwir versi Indonesia-Arab diterjemahkan dengan menggunakan wazan fa'ala. Imbuhan me-kan merupakan salah satu bentuk dari kata kerja transitif. Begitu pula wazan fa'ala di dalam bahasa Arab digunakan untuk